Targeted Near-Infrared Fluorescence Imaging With Iodized Indocyanine Green in Preoperative Pulmonary Localization: Comparative Efficacy, Safety, Patient Perception With Hook-Wire Localization - Ding, Ning; Wang, Kefei; Cao, Jian; Hu, Ge; Wang, Zhiwei; Jin, Zhengyu (Frontiers in Oncology, 2021)
Background: Precise preoperative localization is of great importance to improve the success rate and reduce operation time of VATS surgery. This study aimed to assess the efficacy, safety, patient perception between CT-guided indocyanine green(ICG) preoperative localization of lung nodule and hook wire localization. Methods：65 patients with 85 nodules scheduled for clinically indicated pulmonary nodule underwent ICG in this study, and 92 patients with 95 nodules localized by conventional hook wire served as controls. Both hook wire localization and ICG injection were performed under CT guidance. Successful targeting rate, success rate in the operative field, incidence rate of complications and respiratory pain score were recorded and compared. Results: The successful targeting rate for both groups is 100%, however, due to hook wire dislodgement, the success rate in the VATS operation field of the hook wire group(95.6%) is lower than that of the ICG group(100%), with no significant difference(p=0.056). The overall complication rate of the hook wire group(37.0%) is significantly higher than the ICG group(35.4%)(p=0.038).The mean respiratory pain score of the hook wire group is 3.70±1.25, which is significantly higher than that of the ICG group(2.85±1.05)(p<0.001). Conclusions: ICG composed with contrast mixture are superior to the conventional hook wire preoperative lung nodule localization procedure, with a lower complication rate, lower pain score, and relatively higher success rate. ICG is a promising alternative method for the pulmonary nodule preoperative localization.